2021
DOI: 10.3390/su13063343
|View full text |Cite
|
Sign up to set email alerts
|

An Internet of Things Approach for Water Efficiency: A Case Study of the Beverage Factory

Abstract: There is a lack of knowledge among food manufacturers about adopting the Internet of Things (IoT)-based water monitoring system and its ability to support water minimisation activities. It is therefore necessary to investigate the applicability of IoT-based real-time water monitoring systems in a real food manufacturing environment to pursue water-saving opportunities accordingly. This article aims to propose an architecture of an IoT-based water-monitoring system needed for real-time monitoring of water usage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…This would facilitate the evaluation of food waste measures and predict what measures are more effective. New technologies, such as the application of Internet of Things (IoT)-based monitoring systems, could help us to more efficiently perform measurements along the food chain [ 47 ]. More complete information on the impacts of measures would make incentives for reducing food waste at various levels along the food chain more visible.…”
Section: Discussionmentioning
confidence: 99%
“…This would facilitate the evaluation of food waste measures and predict what measures are more effective. New technologies, such as the application of Internet of Things (IoT)-based monitoring systems, could help us to more efficiently perform measurements along the food chain [ 47 ]. More complete information on the impacts of measures would make incentives for reducing food waste at various levels along the food chain more visible.…”
Section: Discussionmentioning
confidence: 99%
“…FLW imply an inefficient use of resources (i.e., water, energy, food) within the agri-food systems with detrimental impacts on food security levels. Policy measures to contain FLW at different stages of the food production and supply chains are crucial to reduce the impacts on food security [2,34,36]. It is important that future research examines the interrelations between FLW and food security.…”
Section: Discussionmentioning
confidence: 99%
“…Scaling to industrial production has been tested, and these are shown in Table 1, which leads us to identify the more important challenges of localising processing options and enhancing connectivity across BSFL supply chains so that circular economies can develop [30,31]. The application of Industry 4.0 including the Internet of Things (IoT), robotics and automation, and big data analytics will enable data collection for assurance, analysis for quality, control for improved productivity, and better-informed decision-making with regard to the optimisation of the BSFL production [32,33]. Adopting an Industry 4.0 approach will deliver less resource wastage, and automated processes such as temperature control could increase the BSFL productivity in processing the food waste.…”
Section: Innovation and Industry 40 For Bsfl Productionmentioning
confidence: 99%